The Effects of Tool Position, Coating and Cutting Parameters on Forces, Power, MRR and Wear in Face Milling of Stellite 6 - Bagci, Eyup; Aykut, Seref (SPRINGER HEIDELBERG, 2014)
High-speed milling is known to be an advanced machining process increasingly used for modern materials such as nickel- or cobalt-based superalloys. In this paper, the effect of machining parameters including cutting velocity, feed rate and depth of cut on tool wear, material removal rate, cutting forces and power in symmetric and asymmetric face milling of Stellite 6 with coated and uncoated inserts has been studied. One hundred and eighty experiments were carried out with different machining conditions. The settings of milling parameters were determined by using general full factorial design method. The analysis of variance was employed to analyze the effect of machining parameters on the cutting forces. Cutting speeds' effect on cutting forces has not been observed. The depth of cut has greater influence on the resultant cutting forces. Experiments show that the milling forces on Z-axis direction (F (z) ) are the highest for symmetric face milling in the table system of cutting forces. The depth of cut and feed rate have greater influence on the resultant cutting forces in the symmetric and asymmetric face milling processes for PVD-coated and uncoated inserts. It is found that if feed rate and depth of cut are increased, the cutting power would increase and the asymmetric milling strategy becomes superior when compared to symmetric milling with more cutting power. Additionally, the end of tool life is more frequently caused by chipping and breakage of the edge rather than regular tool wear because face milling is an interrupted cutting operation.
Keywords: Face milling; Cutting forces; Specific energy; Cutting power; Wear; MRR; ANOVA; SURFACE-ROUGHNESS; MICROSTRUCTURE; LIFE; Science & Technology - Other Topics